Developmental endothelial locus-1 in cardiovascular and metabolic diseases: A promising biomarker and therapeutic target - Zhao, Mengmeng; Zheng, Zihui; Li, Chenfei; Wan, Jun; Wang, Menglong (Frontiers in Immunology, 2022)
Cardiovascular and metabolic diseases (CVMDs) are a leading cause of death worldwide and impose a major socioeconomic burden on individuals and healthcare systems, underscoring the urgent need to develop new drug therapies. Developmental endothelial locus-1 (DEL-1) is a secreted multifunctional domain protein that can bind to integrins and play an important role in the occurrence and development of various diseases. Recently, DEL-1 has attracted increased interest for its pharmacological role in the treatment and/or management of CVMDs. In this review, we present the current knowledge on the predictive and therapeutic role of DEL-1 in a variety of CVMDs, such as atherosclerosis, hypertension, cardiac remodeling, ischemic heart disease, obesity, and insulin resistance. Collectively, DEL-1 is a promising biomarker and therapeutic target for CVMDs.